2023
DOI: 10.1186/s12886-022-02734-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of MicroShunt implantation versus standard trabeculectomy for open-angle glaucoma (a SIGHT study): study protocol of a multicentre randomised controlled trial

Abstract: Background Trabeculectomy is the “gold standard” initial surgical procedure for open-angle glaucoma worldwide. During the last decade, the introduction of less invasive procedures, including new bleb-forming surgery such as the MicroShunt, has altered the approach of glaucoma management. At present, there is insufficient evidence comparing the effectiveness between these procedures nor versus trabeculectomy. Furthermore, there is no data available on patient impact and cost-effectiveness. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The inferiority of MicroShunt in this study may be attributed to a lower dosage of MMC (0.2 mg/mL), as other studies have reported better success for the MicroShunt with higher dose of antifibrotic agents 208,214,215 . A new multicenter RCT in The Netherlands will explore the noninferiority of MicroShunt to trabeculectomy with a primary endpoint of IOP reduction 1 year after surgery 216 . The MicroShunt provides significant reduction in IOP and medical therapy with improved safety profile, but longitudinal prospective data on the device will be important in assessing its long-term safety and efficacy in glaucoma treatment.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The inferiority of MicroShunt in this study may be attributed to a lower dosage of MMC (0.2 mg/mL), as other studies have reported better success for the MicroShunt with higher dose of antifibrotic agents 208,214,215 . A new multicenter RCT in The Netherlands will explore the noninferiority of MicroShunt to trabeculectomy with a primary endpoint of IOP reduction 1 year after surgery 216 . The MicroShunt provides significant reduction in IOP and medical therapy with improved safety profile, but longitudinal prospective data on the device will be important in assessing its long-term safety and efficacy in glaucoma treatment.…”
Section: Introductionmentioning
confidence: 85%
“…208,214,215 A new multicenter RCT in The Netherlands will explore the noninferiority of MicroShunt to trabeculectomy with a primary endpoint of IOP reduction 1 year after surgery. 216 The Micro- Shunt provides significant reduction in IOP and medical therapy with improved safety profile, but longitudinal prospective data on the device will be important in assessing its long-term safety and efficacy in glaucoma treatment.…”
Section: Medications Versus Trabeculectomymentioning
confidence: 99%